FOXE1 inhibits cell proliferation, migration and invasion of papillary thyroid cancer by regulating PDGFA. (1st August 2019) - Ding, Zheng; Ke, Ronghu; Zhang, Yong; Fan, Youben; Fan, Jianxia
Abstract: Purpose: Forkhead box E1 (FOXE1) plays an important role in the development, proliferation and differentiation of thyroid cells. However, the biological functions of FOXE1 in papillary thyroid cancer (PTC) remain unclear. Materials and methods: In this study, the level of FOXE1 expression was examined in human PTC tissues and cells. Then, the high expression of FOXE1 was specifically silenced by RNA interference in vitro. Subsequently, FOXE1-shRNA was transfected into PTC cells (TPC-1 and K1). The effects on cell proliferation, migration and invasion were evaluated. In addition, FOXE1 targets were screened by cDNA microarray assays. The correlation between the expression of target gene platelet-derived growth factor A (PDGFA) and clinicopathological features of PTC patients was analysed. Results: FOXE1 is highly expressed in PTC tissues and PTC cell lines. The silencing of FOXE1 significantly promotes PTC cell proliferation, migration and invasion in vitro. The cDNA microarray analyses show that PDGFA is a critical downstream target gene of FOXE1 in PTC cells. It was also observed that PDGFA is negatively regulated by FOXE1 in PTC. The clinical data indicate that the low expression level of PDGFA is correlated with the small size of PTC. Conclusion: Collectively, the results indicate for the first time that high expression of FOXE1 may function as a tumour suppressor in the early stage of PTC and restrain the proliferation, migration and invasion of PTC by negatively regulating PDGFA expression. Thus, FOXE1 could serve as a prognostic biomarker for PTC. Highlights: This study indicates that FOXE1 may function as a tumour suppressor in the early stage of PTC. The research is the first to illustrate why some PTCs potentially maintain the inertia of growing very slowly. The present study is expected to provide a new predicted and therapeutic strategy for PTC.